Rh and other blood groups in the Peruvian Indians - Reynafarje, César (1957)
It reports on the study of blood groups in 800 natives of the central Peruvian Andes, held in the ABO, MNSs and Rh-Hr systems. Namely the salient features are highlighted: a high percentage of group O, almost no subject Rho (D) negative, relatively high percentage of Rz (CRE) type and prevalence of N. M factor on a brief comparative analysis is made between data obtained in the present study and encontrads other native American groups, highlighting the similarity between them. The existence of the A2 factor is discussed.